(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This article presents data on the impact of mental work on the cardiovascular and central nervous systems of workers, including changes in blood pressure, PCL, red blood cell count, and the impact on visual response and auditory motor analyzers during various types of mental activity. Comprehensive hygienic and physiological studies enabled the development of measures to improve performance and prevent illnesses in workers in various professions. The results of these studies served as the basis for developing preventive measures.